KUALITAS PELAYANAN RUMAH SAKIT UMUM DAERAH DR. H. MOH. ANWAR KABUPATEN SUMENEP - Wardatunnisa Firdaus Azizah; Sri Wibawani (Jurnal Penelitian Administrasi Publik, 2021)
ABSTRACT This research is based on the phenomenon of the number of outpatient data at Dr. Hospital. H Moh Anwar, Sumenep Regency, which occupies the largest hospital in Sumenep Regency. It is known that public services must have the best service to the community in order to provide good service quality. The research method used is descriptive quantitative with data collection techniques in the form of questionnaires. This research is measured based on public service standards according to Law No. 25 of 2009 concerning public services. Zeithaml (1990) suggests nine dimensions that must be considered in measuring the quality of public services, namely: tangible, reliability, responsiveness, compatnce, courtesy, credibility, security, communication and under standing the customer. The research population in this study was 278. The results obtained based on the quality of service in RSUD Dr. H Moh Anwar Sumenep District from 9 variables, namely: 1) The quality of patient care at Dr. RSUD. H Moh Anwar, the majority of Sumenep Regency is in the very quality category. 2) The quality of patient care in the Tangible sub-variable is mostly categorized as very high-quality. 3) The quality of patient care in the reliability sub-variable is in the category of very high quality. 4) The quality of patient care in the Responsiveness sub-variable is mostly in the quality category. 5) The quality of patient care in the competence sub-variable is in the category of very high quality. 6) The quality of patient care in the courtesy sub-variable is in the category of very high quality. 7) The quality of patient care in the credibility sub-variable is mostly in the quality category. 8) The quality of patient care in the security sub-variable is mostly categorized as less qualified. 9) The quality of patient care in the communication sub-variable is mostly in the quality category. 10) The quality of patient care in sub-understanding the customer is mostly categorized as less qualified Keywords: Service, Service Quality